2019
DOI: 10.1371/journal.pone.0217548
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular markers in retinal detachment—From hyperreflective points to stem cells and inflammation

Abstract: Purpose Retinal detachment (RD) is one of the most frequently diagnosed ophthalmologic conditions requiring prompt surgical intervention. Combination of proper surgical technique and new diagnostic markers, both clinical and molecular, can help improve the diagnosis and prognosis of RD treatment. Methods 12 patients with rhegmatogenous RD (rRD) were included into the study after obtaining patient consent and Regional Ethical Approval (average age: 58.1 ± 17.4 years). OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…25 Although the causal relationship between decreased CCP blood flow and the defect of the photoreceptor layer in macula-off RRD could not be elucidated in this retrospective study, studies have shown that the subretinal fluid (SRF) contains inflammatory cytokines and other factors that contribute to triggering and enhancing the inflammatory and immune responses. 26,27 The bloodretina barrier may also get damaged during RD, similar to the RPE cells, 28,29 and vasoconstrictors, such as endothelin, are known to be present in the SRF. 30,31 Taken together, we could hypothesize that, after RRD occurred, the detached neurosensory retina might be damaged by inflammatory cytokines in the SRF, and CCP blood flow might be impaired because of such cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although the causal relationship between decreased CCP blood flow and the defect of the photoreceptor layer in macula-off RRD could not be elucidated in this retrospective study, studies have shown that the subretinal fluid (SRF) contains inflammatory cytokines and other factors that contribute to triggering and enhancing the inflammatory and immune responses. 26,27 The bloodretina barrier may also get damaged during RD, similar to the RPE cells, 28,29 and vasoconstrictors, such as endothelin, are known to be present in the SRF. 30,31 Taken together, we could hypothesize that, after RRD occurred, the detached neurosensory retina might be damaged by inflammatory cytokines in the SRF, and CCP blood flow might be impaired because of such cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 37 of the studied cytokines were significantly higher in the subretinal fluid of RRD patients compared to the vitreous of non-RRD patients. [36] Our study has some limitations, such as the complexity and a high number of cytokines that need further investigations to detect their relationships more exactly. Retinal detachments present with variable clinical features, which might contribute to the multiplex variations of cytokines in the fluids.…”
Section: Plos Onementioning
confidence: 93%
“…There is increasing evidence that in the presence of RRD, the activation of inflammatory processes occurs, in particular when it is associated with choroidal detachment [5,6]. The surgeries themselves, both scleral buckle (SB) and pars plana vitrectomy (PPV), induces an inflammatory response as demonstrated by an increase of aqueous flare values, from day one up to three months post-operatively with the peak value observed at post-operative day seven [7].…”
Section: Introductionmentioning
confidence: 99%